LEADERSHIP SPEECH IN INSTITUTIONAL INTERACTION: AN ANALYSIS OF PRAGMATIC AND SOCIAL PROCESSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Analysis of pragmatic and social processes of speech in this process of institutional communication. In targeted speech analysis, the guide consists of determining the connection between speech acts, communicative strategies, and social context. The research methodology is based on the theory of speech acts, discourse analysis, and sociolinguistic research. Analysis of the organization's official meetings, official assignments, and leaders' speeches before the team as empirical material. The study shows that software helps to regulate hierarchical relationships, ensure the importance of collective activity, and manifests itself as a means of communication. Language units acquired in the leader's speech social distance.